Chemical characterization of wheat-based waste derived from a pharmaceutical process for its potential valorization - Ciriaco, Lidia; Izzo, Luana; Graziani, Giulia; Ferraro, Maria Grazia; Piccolo, Marialuisa; Ciampaglia, Roberto; Maglione, Barbara; Palladino, Roberta; Albarella, Simone; Romano, Eugenia; Ritieni, Alberto; Irace, Carlo; et al. (Frontiers in Chemistry, 2024)
We report the analysis and characterization and the preliminary biological evaluation, of both liquid and solid wastes obtained from the processing of wheat (Triticum vulgare) to produce the most iconic phytostimulin-based pharmaceutical products. The study aims to verify whether the waste can be reused in another process and not destined to its simple destructive disposal. In this perspective, we first carried out an in-depth chemical-physical analysis of the waste together with a biocompatibility evaluation to plan the feasible final choice of waste destination.The liquid and solid waste derived from the processing of wheat extract were analyzed and characterized through ultra-high-performance liquid chromatography coupled with high-resolution Orbitrap mass spectrometry (UHPLC Q-Orbitrap HRMS). Results highlight that ferulic acid represent the most abundant phenolic compound for solid waste with a content of 89.782 mg/Kg and dihydroferulic acid is the predominant for liquid waste (6.24 mg/L). These concentrations represent 55.87% and 84.39% of the total concentration of bioactive compounds for liquid and solid waste, respectively. The antioxidant activity registered for the solid extract was 8.598 and 7.262 mmol trolox/kg, respectively for ABTS and FRAP assays. The total phenolic content (TPC) in the liquid extract undergoes a significant percentage reduction compared to the solid waste.As regards toxicity, both liquid and solid wastes were investigated in vitro preclinical models of human skin (HaCaT cells and HDFa) after 24, 48, and 72 hours of exposure. No cytotoxic effect was noted even at the highest tested concentration (100 µg/mL) at 72 h. Overall, considering its chemo-physical features and active ingredients, we believe that this waste is highly reusable as a starting material for the development of cosmeceutical products. Thus, this study allows us to motivate the destination of the waste of the production in a recyclable raw material for additional industrial processes, thereby promoting an eco-friendly circular economy operation.